Unlocking Financial Innovation: A Deep Dive into Blockchain-based Crowdfunding - Pragati Mahale; Pranit Morab (MultiTech Publisher, 2023)
This study focuses on addressing current issues in China's equity crowdfunding practices. By harnessing blockchain technology, it can serve as a secure and cost-effective solution for registering stocks and shares in crowdfunded firms. Blockchain simplifies equity transactions in crowdfunding, enhancing their liquidity and ease of transfer. It enables direct peer-to-peer interactions between investors and entrepreneurs, addressing regulatory compliance and fund security concerns. Blockchain can be utilized to create a transparent voting system for crowdfunders, empowering them in corporate governance and safeguarding the interests of small investors. Additionally, it aids regulators in monitoring market conditions and supporting regulatory efforts, including investor management and anti-money laundering measures.